Antibiotic Resistance Phenotypes of Klebsiella pneumonia in Urinary Tract Infection among Patients attending a Tertiary Healthcare Facility in Ekiti State, Nigeria - A. O. , Ajayi; G. O., Daramola (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Urinary tract infections (UITs) are the most common infectious disease worldwide with significant morbidities, both in clinical and community settings. The Klebsiella pneumonie is a leading cause of UTIs in clinical settings with significant complications and morbidity. The use of antibiotics for treatment of UTIs increases the risk of emergence of antibiotic resistance. This present study was carried out to determine the susceptibility of K. pneumonia isolates recovered from suspected cases of UTIs at a tertiary clinical facility in Ekiti State, Nigeria. K. pneumonia were isolated from urine samples of patients referred to the microbiology laboratory of the healthcare facility. The isolates were identified using standard biochemical tests. Subsequently, the bacterial isolates were subjected to antibiotic susceptibility tests via the agar disk diffusion method using a panel of twelve (12) antibiotics which included the following: tetracycline (10µg), cotrimoxazole (25 µg), gentamicin (10 µg), cefuroxime (30 µg), chloramphenicol (10 µg), ceftriaxone (30 µg), cefotaxime (30 µg), ceftazidime (30 µg), ciprofloxacin (5 µg) and amikacin (30 µg), vancomycin (30 µg) and meropenem (30 µg). This results showed that all the isolates demonstrated resistance to cefuroixime, ceftriaxone, ceftazidime and vancomycin. The organisms also showed considerable resistance to tetracycline 24 (92.3%), cotrimoxazole 21 (80.8%), meropenem 25 (96.2%) and amikacin 20 (76.9%). Resistance to chloramphenicol was the least with 8 (31.0%) of the isolates showing reduced susceptibility to the antibiotic. Twenty four (14) different antibiotic resistance patterns were observed among the isolates. This study showed that bacterial uropathogens recovered from the patients showed high resistance to antibiotics. The findings in this study should enable clinicians to prioritize antimicrobial stewardship in management of UTIs in clinical settings.